PENGARUH BUDAYA ORGANISASI HIRARKI TERHADAP KOMITMEN MELALUI IKLIM ORGANISASI PADA KANTOR IMIGRASI KELAS I KHUSUS SURABAYA - EKASIWI HADIARTI, WINDY (Jurnal Ilmu Manajemen (JIM), 2018)
This research aims to know and explain the influence of Hierarchy Culture on commitment with organizational climate as intervening variable on employee at Kantor Imigrasi Kelas I Khusus Surabaya. This research is a type of causal research that uses a quantitative approach with a population of 136 people and sampling techniques using simple random sampling with a sample of 102 employees,but the questionnaire returned as much as 93. Data analysis techniques using the assistance software smartPLS.The result of the research that hierarchy organization and organizational climate positive and significant to organizational commitment and culture positive and significant to organizational climate.While organizational climate is not able to be an intervening variable between organizational culture hierarchy and commitment. Keywords:hierarchy organizational culture, organizational climate, commitment